Sustentabilidade da monocultura do milho em assentamentos rurais no município de Simão Dias – SE - Araujo, Clezyane Correia (2018)
The agricultural model imposed in the 80 and used globally to the present day is highly questionable as to its sustainability. The need to measure and evaluate the sustainability of agricultural systems encouraged the development of several evaluation tools and methodologies that could make this process viable. In this sense, sustainability indicators are important tools of analysis that use environmental impact assessment models in agricultural activities. Thus, the objective of the present research was to estimate the level of sustainability of the corn farm in settlements in the municipality of Simão Dias / SE, by means of environmental impact indicators. The present research is based on the hypothesis that monoculture contributes to the reduction of the level of sustainability in agrarian reform settlements, intensifying the impact that this system of production brings in the social, economic and environmental dimension. The study was divided in two stages of research: bibliographical and field, with the intention of evaluating the environmental and socioeconomic impact of the family units with maize production in settlements in the municipality of Simão Dias / SE, using the method Weighted Impact Assessment (APOIA-Novo Rural) which identified the level of environmental impact that the activity causes to the environment, as well as the limiting and potential aspects of its economic and social development. As a result, it was verified that the agricultural specialization that took place in the settlements after the consolidation of the monoculture as a production system compromised the environmental performance, generating unsatisfactory sustainability indices, bringing consequences to the producers (social scope) and to the environment (ecological scope).